PENGEMBANGAN MEDIA PEMBELAJARAN PROTOTYPE LIFT BERBASIS PLC PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XII TITL DI SMK NEGERI 14 MEDAN - Kevin Boijogy Batubara; Wanapri Pangaribuan (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract This study aims: (1) To find out students' responses to learning media for lift prototypes based on PLC Omron type CPM1A for electric motor installation subjects on Forward-Reverse electric motor control material for class XII TITL SMK Negeri 14 Medan (2) To find out the results from developing learning media by designing learning media for prototype lifts based on PLC type Omron type CPM1A on electric motor installation subjects for class XII SMK Negeri 14 Medan, and (3) To determine the feasibility of learning media for prototype lifts based on PLC type Omron type CPM1A for eyes electric motor installation lessons class XII SMK Negeri 14 Medan odd semester 2022/2023 academic year. The type of research used is Research and Development (R&D) with the ADDIE research model. The ADDIE research model includes five stages, namely the first analysis which includes needs analysis, the second design, namely designing mechanical, electrical and wiring as well as program design for learning media for prototype elevators, the third development, namely developing learning media by designing and building a three-floor PLC-based elevator prototype that has been designed to do a feasibility test in order to get input from media experts and material experts, the fourth is implementation, namely implementing the product to get responses from users (students) to the prototype lift learning media that has been developed, the fifth evaluation, namely evaluating modules based on some input from experts and responses user. The instruments used in this study were due diligence questionnaires and user response questionnaires. The validity used is based on the opinions of two material experts and two media experts. The results of this study can be seen: (1) This development research produces a product in the form of a PLC-based lift prototype learning media for the class XII TITL electric motor installation subject at SMK Negeri 14 Medan. (2) The feasibility of the prototype elevator learning media in terms of material experts gets a score of 87.50% of the maximum percentage of 100% and is categorized as "Very Eligible". In terms of media experts, it gets a score of 97.50% of the maximum percentage of 100% and is categorized as "Very Decent". The results of user responses (students) in the "Very Good" category obtained an average percentage score of 92%. Then the developed PLC-based lift prototype learning media is declared feasible to use. The recommendation in this study is that the development of media for this elevator prototype can be carried out again in other subjects by adding several work systems so that it can further increase student motivation and enthusiasm for learningÂ Key Words: Development of Learning Media, ADDIE, Lift Prototype, Omron PLCÂ AbstrakPenelitian ini bertujuan untuk: (1) Untuk mengetahui respon siswa terhadap media pembelajaran prototype lift berbasis PLC jenis Omron type CPM1A untuk mata pelajaran instalasi motor listrik pada materi pengontrolan motor listrik secara Forward-Reverse kelas XII TITL SMK Negeri 14 Medan (2) Untuk mengetaui hasil dari pengembangan media pembelajaran dengan merancang bangun media pembelajaran prototype lift berbasis PLC jenis Omron type CPM1A pada mata pelajaran instalasi motor listrik kelas XII SMK Negeri 14 Medan, dan (3) Untuk mengetahui tingkat kelayakan media pembelajaran prototype lift berbasis PLC jenis Omron type CPM1A untuk mata pelajaran instalasi motor listrik kelas XII SMK Negeri 14 Medan semester ganjil tahun ajaran 2022/2023. Jenis penelitian yang digunakan ini adalah Research and Development (R&D) dengan model penelitian ADDIE. Model penelitian ADDIE meliputi lima tahapan yaitu pertama analysis yang meliputi analisis kebutuhan, kedua design yaitu mendesain mekanik, elektric dan wiring serta desain program untuk media pebelajaran prototype lift, ketiga development yaitu mengembangkan media pembelajaran dengan merancang bangun sebuah prototype lift tiga lantai berbasis PLC yang sudah didesain untuk dilakukan uji kelayakan agar mendapatkan masukan oleh ahli media dan ahli materi, keempat implementation yaitu menerapkan produk untuk mendapatkan respon dari pengguna (siswa) terhadap media pembelajaran prototype lift yang telah dikembangkan, kelima evaluation yaitu mengevaluasi modul berdasarkan beberapa masukkan dari para ahli serta respon pengguna. Instrumen yang digunakan pada penelitian ini adalah angket uji kelayakan dan angket respon pengguna. Validitas yang digunakan adalah berdasarkan pendapat dari dua ahli materi dan dua ahli media. Hasil Penelitian ini dapat diketahui: (1)Penelitian pengembangan ini menghasilkan produk berupa media pembelajaran prototype lift berbasis PLC pada mata pelajaran instalasi motor listrik Kelas XII TITL di SMK Negeri 14 Medan. (2) Kelayakan media pembelajaran prototype lift ditinjau dari ahli materi mendapatkan skor 87,50% dari persentase maksimum sebesar 100% dan dikategorikan â€œSangat Layakâ€. Ditinjau dari ahli media mendapatkan skor 97,50% dari persentase maksimum sebesar 100% dan dikategorikan â€œSangat Layakâ€. Hasil respon penngguna (siswa) dengan kategori â€œSangat Baikâ€ memperoleh rata-rata presentase skorÂ  92%. Maka media pembelajaran prototype lift berbasis PLC yang dikembangkan dinyatakan layak untuk digunakan. Rekomendasi pada penelitian ini adalah pengembangan media terhadap prototype lift ini dapat dilakukan lagi pada mata pelajaran lainnya dengan menambahkan beberapa sistem kerjanya sehingga dapat lebih meningkatkan motivasi dan semangat belajar siswa.Kata Kunci: Pengembangan Media Pembelajaran, ADDIE, Prototype Lift, PLC Omron